A Fibromyxoid Stromal Response is Associated with Muscle Invasion in Canine Urothelial Carcinoma. (May 2019) - de Brot, S.; Grau-Roma, L.; Stirling-Stainsby, C.; Dettwiler, M.; Guscetti, F.; Meier, D.; Scase, T.; Robinson, B.D.; Gardner, D.; Mongan, N.P.
Summary: Canine urothelial carcinoma (UC) is the most common type of cancer of the lower urinary tract and tends to affect elderly neutered female dogs, with a high predisposition for Scottish terriers. Tumour stroma, inflammation and necrosis are poorly characterized in canine UC and their role as prognostic factors is unknown. The aims of this study were to (1) assess histologically 381 canine UCs, with emphasis on myxoid tumour stroma, inflammation and necrosis and (2) assess possible associations between these features and the available epidemiological data as well as bladder wall muscle invasion. In 103 of 381 (27%) cases, the stroma was mixed collagenous and myxoid (fibromyxoid), which was strongly associated with invasive growth of muscle ( P <0.0001). Peritumoural and intratumoural inflammation was present in 308 of 345 (89%) and 287 of 381 (75%) cases, respectively, and was mostly mild and lymphoplasmacytic. One hundred and fifteen of the 381 (30%) cases showed a variable eosinophilic inflammation and 58 of 381 (15%) presented with formations of one or several lymphoid follicles. Twenty-four percent (91 of 381) of cases had tumour necrosis, which was typically mild. In 83 of 91 (91%) cases, the necrosis was comedo-like. Moderate to severe tumour necrosis was associated with the presence of moderate to predominant fibromyxoid tumour stroma ( P <0.02). The results of this study indicate that fibromyxoid stroma is common in canine UC and is a strong indicator for invasive growth of muscle, which is consistent with a poor prognosis. Based on histomorphology, tumour necrosis in canine UC is best described as comedonecrosis.